An Examination of Dental Prostheses as Tools for Individual Identification - Alaa, Zaid; Hameed, Reem Majeed; Tektook, Nihad Khalawe; N.Medatwal, Shailesh (Journal of Neonatal Surgery, 2025)
Dentistry offers significant support to law enforcement in the detection and resolution of crimes, as well as in clinical proceedings. Prosthodontics, as a specialised branch, can play a crucial role in identifying individuals. Dental prostheses can serve as valuable tools in identifying individuals who have lost their memory, are in unconscious states, or in recognising the bodies of those who have died in accidents, disasters, or natural calamities. Forensic odontology plays a vital role in identifying individuals in cases involving criminal investigations, mass disasters, or unrecognisable remains. Among the various tools available to forensic experts, dental prostheses have emerged as significant identifiers. Prosthodontics, a specialized branch of dentistry, provides unique markers through customized prosthetic devices such as dentures, bridges, and implants. These dental appliances, when appropriately marked or labeled, can offer critical information regarding a person's identity, especially in cases of memory loss, unconsciousness, or fatalities in accidents and natural calamities. This review aims to explore the forensic relevance of dental prostheses, their identification potential, and the methods used for labelling and recording them. Dental prostheses, such as dentures, crowns, bridges, and implants, are not only functional replacements for missing oral structures but can also serve as valuable forensic tools. In forensic dentistry, these prosthetic devices can carry unique identifiers such as serial numbers, embedded barcodes, or customised inscriptions, aiding in the identification of unknown individuals, especially in cases involving trauma, memory loss, unconsciousness, or mass disasters. This paper examines the role of dental prostheses in individual identification and discusses various methods used to mark and record these devices for forensic and clinical purposes. Dentistry offers significant support to law enforcement in the detection and resolution of crimes, as well as in clinical proceedings. Prosthodontics, as a specialised branch, can play a crucial role in the identification of individuals. Dental prostheses can serve as valuable tools in identifying individuals who have lost their memory, are in unconscious states, or in recognising the bodies of those who have died in accidents, disasters, or natural calamities.